2016
DOI: 10.18632/oncotarget.12829
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of 3D-printed-step-bolus in post-total-mastectomy electron conformal therapy

Abstract: The 3D-printed boluses were used during the radiation therapy of the chest wall in six patients with breast cancer after modified radical mastectomy (MRM). We measured the in-vivo skin doses while both conventional and 3D-printed boluses were placed on the chest wall and compared the mean doses delivered to the ipsilateral lung and the heart. The homogeneity and conformity of the dose distribution in the chest wall for both types of boluses were also evaluated. The uniformity index on the chest skin was improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…Several previous works had employed ABS filament because its physical properties closely resemble those of water [17,25,26]. However, ABS filament can undergo considerable deformation during cooling [16,18,19]; thus, we employed PLA filament. The results of this study demonstrate slight geometric errors between the CT scanned image of the anthropomorphic head phantom and the 3D-printed phantom, mostly in the bottom region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous works had employed ABS filament because its physical properties closely resemble those of water [17,25,26]. However, ABS filament can undergo considerable deformation during cooling [16,18,19]; thus, we employed PLA filament. The results of this study demonstrate slight geometric errors between the CT scanned image of the anthropomorphic head phantom and the 3D-printed phantom, mostly in the bottom region.…”
Section: Discussionmentioning
confidence: 99%
“…Ju et al suggested a new system for manufacturing a range compensator in proton therapy, using an industrial 3D printer with ultraviolet curable acrylic plastic [15]. Park et al fabricated a patientspecific customized bolus, using a low-cost personal 3D printer with a polylactic acid (PLA) filament, and evaluated its feasibility for posttotal-mastectomy electron conformal therapy [16]. Further, Ehler et al demonstrated the construction of a patient-specific phantom, using a 3D printer with an acrylonitrile butadiene styrene (ABS) filament for dosimetry [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radical mastectomy under general anesthesia is a widely-used therapy in patients with breast cancer [ 13 - 15 ]. It has been known that breast cancer patients undergoing radical mastectomy experience severe sleep disturbance and fatigue [ 16 , 17 ], which might lead to prolonged convalescence and additional hospital costs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the emergence of 3D printing technology in various arenas in medicine has garnered similar interest in radiation oncology. A significant amount of effort into 3D printing has been utilized for patient‐specific devices, which include: bolus for electron treatments, compensators for photon treatments, and patient immobilization . 3D printing in brachytherapy applicators has also been investigated.…”
Section: Introductionmentioning
confidence: 99%